Economics of poverty inequality and discrimination - Wolff, Edward Nathan. (South-Western College, 1997)
This book is divided into five parts: Income inequality and poverty: Measurement and trends; The role of labor markets; Wealth and savings; Discrimination; and The role of public policy on inequality.